The nature and chronology of human occupation at the Galerias Bajas, from Cueva de Ardales, Malaga, Spain - Ramos-Munoz, Jose; Cantalejo, Pedro; Blumenröther, Julia; Bolin, Viviane; Otto, Taylor; Rotgaenger, Miriam; Kehl, Martin; Nielsen, Trine Kellberg; Espejo, Mar; Fernandez-Sanchez, Diego; Moreno-Marquez, Adolfo; Vijande-Vila, Eduardo; et al. (PLoS ONE, 2022)
The Cueva de Ardales is a hugely important Palaeolithic site in the south of the Iberian Peninsula owing to its rich inventory of rock art. From 2011-2018, excavations were carried out in the cave for the first time ever by a Spanish-German research team. The excavation focused on the entrance area of the cave, where the largest assemblage of non-figurative red paintings in the cave is found. A series of 50 AMS dates from the excavations prove a long, albeit discontinuous, occupation history spanning from the Middle Palaeolithic to the Neolithic. The dating of the Middle Palaeolithic layers agrees with the U/Th dating of some red non-figurative paintings in the entrance area. In addition, a large assemblage of ochre lumps was discovered in the Middle Palaeolithic layers. Human visits of the cave in the Gravettian and Solutrean can be recognized, but evidence from the Aurignacian and Magdalenian cannot be confirmed with certainty. The quantity and nature of materials found during the excavations indicate that Cueva de Ardales was not a campsite, but was mainly visited to carry out non-domestic tasks, such as the production of rock art or the burial of the dead.
CRIS-Team WoS Importer:2022-09-09